Environmental justice and physical activity: examining disparities in access to parks in Kansas City, Missouri - Vaughan, Katherine B. (Kansas State University, 2011)
Background: Parks are key community assets for promoting physical activity, especially in low income areas where other accessible, low cost resources may not be available. However, some evidence suggests these integral resources are not equitably distributed. The primary purpose of this study was to examine disparities in park availability, features, and quality across socioeconomically and racially diverse census tracts (CTs) in Kansas City, Missouri (KCMO). Methods: All parks in KCMO were mapped using GIS shape files provided by the City of KCMO. Park features and quality were determined via on-site audits using the Community Park Audit Tool. Data from the American Community Survey were used to designate all 174 CTs within KCMO as either low, medium, or high income and percent minority. MANCOVA was used to analyze differences in park availability, features, and quality across income and race/ethnicity tertiles. Results: Low income CTs contained significantly more parks (M=1.46) than medium (M=1.25) or high (M=1.00) income CTs, but also had more quality concerns (e.g., vandalism) per park. High income CTs contained more playgrounds per park (M=.69) than low (M=.62) and medium (M=.52) income tracts. There were more basketball courts per park in high minority CTs (M=.59) than low (M=.13) or medium (M=.30) minority CTs, and more trails per park in low (M=.60) and medium (M=.55) minority CTs than high (M=.39) minority CTs. Finally, there were more sidewalks around parks in low (M=.87) and high (M=.74) income CTs than medium (M=.61) income CTs. Conclusions: This study adds to an important body of literature examining income and racial disparities in access to active living environments. Park availability was greater in low income areas, but several key park characteristics were less common in low income or high minority areas. Future research should consider the quality of park facilities and amenities and the composition of neighborhoods around parks, as well as how disparities in access to park environments are associated with physical activity and health outcomes. Public health and parks and recreation researchers and practitioners should work together to examine policies that contribute to and that might rectify disparities in access to safe and attractive parks and open spaces.
Keywords: Environmental justice; Physical jctivity; Obesity; Parks; Built environment; Public health; Environmental Justice (0619); Public Health (0573)